140:poster The ethics of global COVID-19 vaccine allocation. (28th April 2022) - Berkman, Benjamin E; Miner, Skye; Taylor, Holly; Millum, Joseph; Iyer, Alex; Kahn, Rebecca; Rid, Annette
Abstract : Introduction: Policies to increase global vaccine access involve HICs making ethically fraught tradeoffs between saving lives at home or abroad. Such policies should be justifiable to the affected populations. Yet there is little robust data on whether HIC residents endorse their countries' policy choices. Most existing data asks highly simplified questions, without providing background on the ethical tradeoffs involved. These data do not capture the public's informed views, giving policymakers limited guidance on how to craft international vaccine policy. This paper provides the first nuanced data on the informed views of a representative sample of the U.S. public about providing COVID vaccine to poorer countries. Methods: This study involved two interventions: a description of ethical arguments for/against providing vaccine to poorer countries and visuals depiction of ethically relevant tradeoffs about providing vaccine to poorer countries at different time points in the US vaccination campaign. A representative sample of 4000 U.S. adults were surveyed, divided evenly into four arms: 1) arguments only; 2) tradeoffs only; 3) both interventions; 4) no interventions. Results: Across all four arms, people are more willing to donate vaccines than previously reported, with generosity increasing over time. 43% of respondents were willing to share at an early timepoint when supply was extremely limited, increasing to 54% and 71% at intermediate and current timepoints, respectively. Some specific variables (e.g., political affiliation, age, acceptability of masks) were predictive of willingness to donate and endorsement of specific arguments. Discussion: These data can guide policy about providing or keeping U.S. vaccine doses as the world navigates the effects of new variants and the potential need for booster shots in the coming months. Given high levels of willingness to donate, U.S. policy could have initiated global vaccine donations earlier and could be more generous currently.